PERSEPSI TERHADAP DUKUNGAN SOSIAL DITINJAU DARI KARAKTERISTIK REMAJA PANTI ASUHAN DENGAN REMAJA NON - PANTI ASUHAN - Prahastuti, Nurul Fajriyah; Santhoso, Fauzan Heru (Universitas Sahid Surakarta, 2021)
The purpose of this study was to determine differences in the perception of social support among adolescents who are orphanage and non-orphanage. The subject for this study are teenagers age 15-18 years old, 52 of them are living in a foster home while the other 54 are not. Methods of data collection using a Likert attitude scale models. The scale based on the aspects of social support according to Cohen & Syme (1985), which are appraisal support, status support, information support, instrumentational support, companionship support, and motivational support. We hypotheses that there are differences of perception toward social support between teenagers living in foster home and those who are not. The perceived social support scale contains 31-item (Î± = .871). Methods of data analysis using independent sample t-test. Based on the results of the study found that there were no differences in the perception of social support amongadolescents who lived in the orphanage with teenagers who do not live in an orphanage. Based on the results obtained by the value of t = .589, p> .05. Thusconcluded that there was no difference in the perception of social support among adolescents who are orphanage and non-orphanage.